Rural Community Livelihood Around Kerinci Seblat National Park: The Study of Access and Socio-Ecological Relationship of Farming Households in Kota Baru Village, Uram Jaya Sub-district, Lebong Regency, Bengkulu - Sakut Lorista; Arya Hadi Dharmawan (Komunitas: International Journal of Indonesian Society and Culture, 2025)
Forests hold diverse meanings and functions, serving both as natural resources and as critical sources of livelihood for local communities. Beyond providing essential raw materials that sustain human life, forests play a fundamental role in maintaining ecosystem functions and biodiversity. For indigenous peoples and rural populations residing in forest-adjacent areas, forests are deeply embedded in cultural practices and traditional knowledge, shaping their ways of life. In addition to their ecological significance, forests also serve as vital sources of livelihood for local communities. The residents of Kota Baru Village, for instance, depend on the resources of the Kerinci Seblat National Park (TNKS) forest area. Consequently, despite legal restrictions, they continue to engage in agricultural activities within the protected area. This study examines the livelihood structures, access mechanisms, and socio-ecological relationships of farming households surrounding the Kerinci Seblat National Park. Employing a mixed-methods approach, the research findings indicate that resource extraction—through agriculture and forest product collection—contributes significantly to household incomes. Farming households utilize four primary mechanisms to access forest resources within the national park: capital, technology, social identity, and market engagement. This access has fostered intricate socio-ecological relationships between households and the forest, which manifest in three distinct forms: co-existence, subsistence, and exploitation.